Penerimaan Model Teknologi dan Sistem Manajemen Pembelajaran: Sebuah Tinjauan Sistematis - Nazaruddin Ali Basyah; Irham Fahmi; Ismail Ali; Zulfadhli Rusli; Ruaida Abdul Majid (Postgraduate, University of Mataram, 2025)
Learning Management Systems (LMS) have become integral to digital learning, yet their successful implementation depends largely on user acceptance. This study systematically reviews research applying the Technology Acceptance Model (TAM) to understand factors influencing LMS adoption in higher education. Following PRISMA 2020 guidelines, a comprehensive search was conducted across Scopus, Web of Science, and Google Scholar for peer-reviewed empirical studies published in English between 2010 and 2024. A total of 312 records were retrieved, of which 74 duplicates were removed. After screening 238 titles and abstracts, 198 studies were excluded for not meeting the inclusion criteria. The full texts of 40 articles were assessed, and 10 studies were finally included in the qualitative synthesis. The review revealed that Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) remain the most consistent predictors of LMS adoption. External factors such as digital self-efficacy, system quality, institutional support, and social influence also emerged as critical determinants. External factors such as digital self-efficacy, system quality, institutional support, and social influence also emerged as critical determinants. These findings affirm TAM’s continued relevance in educational technology while emphasizing the need to integrate contextual and organizational factors to strengthen predictive accuracy and promote sustainable LMS adoption.